2005
DOI: 10.2519/jospt.2005.35.11.708
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Imaging in Physical Therapist Practice

Abstract: This article presents an overview of current concepts of evidence-based diagnosis using a variety of imaging modalities for a broad spectrum of musculoskeletal conditions and syndromes. There is limited but increasing evidence that physical therapists appropriately use diagnostic studies in clinical practice. Pathology revealed by diagnostic studies must be viewed in the context of the complete examination, as pathology is common in the asymptomatic population. Special Key Words: clinical decision rule, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…Also, the current study found some notable MI practices among the participants such as screening the patients with appropriate CDC before MI referral. The use of the CDC, including the American College of Radiology Appropriateness Criteria, are foundations for deciding on the appropriateness of ordering an MI procedure [ 30 – 32 ]. Moreover, some participants often reviewed the printed images before applying the accompanying report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the current study found some notable MI practices among the participants such as screening the patients with appropriate CDC before MI referral. The use of the CDC, including the American College of Radiology Appropriateness Criteria, are foundations for deciding on the appropriateness of ordering an MI procedure [ 30 – 32 ]. Moreover, some participants often reviewed the printed images before applying the accompanying report.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some participants often reviewed the printed images before applying the accompanying report. Although radiologists are responsible for reporting diagnostic imaging, it is recommended that physiotherapists juxtapose the films, DIR, medical history, and physical examination for comprehensive assessment [ 30 ]. The current authors align with scholars who posit that MI should not be misconstrued as an alternative to detailed medical history and clinical examination [ 3 , 8 , 30 , 31 ]; rather, it should be used as an adjunct for broadening clinical assessment and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ultrasound scanning (USS) has moved from the radiology suite to point-of-care, where physiotherapists can perform real-time diagnostic musculoskeletal sonography [7,8]. Magnetic resonance imaging (MRI) scans are useful when examining subtle musculoskeletal pathologies such as stress fractures, which may have consequences for a physiotherapy plan of care [9]. Also, information from dual-energy X-ray absorptiometry (DEXA), scintigraphy and computed tomography (CT) scans can be used for risk assessment to rule out red flags that may contraindicate the use of some physiotherapy modalities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The physiotherapy programme accreditation standards in the USA and Nigeria now include specific criteria related to diagnostic imaging [2,15]. Therefore, training in MI procedures such as radiography (X-ray), CT scan, MRI, scintigraphy, USS, and DEXA has become relevant for entry-level physiotherapy programmes to prepare students for direct-access practice [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently real time ultrasound imaging has been utilized as an accurate and reliable means of measuring muscle parameters in a non invasive manner [15,16]. Ultrasound imaging is a fast and inexpensive tool that produces excellent images of the musculoskeletal system without the need for radiation [17]. …”
Section: Introductionmentioning
confidence: 99%